IMPLIKASI UNDANG-UNDANG TINDAK PIDANA KEKERASAN SEKSUAL TERHADAP ASPEK PERLINDUNGAN KORBAN - Hertini, Mega Fitri; Karlina, Dina; Herlina, Hj.; Ismawati, Sri; Maryana, Lina; Addhauly, Dio Aswad (Faculty of Law, Universitas Pasundan, 2022)
This research aims to review the implications of Anti-Sexual Violence Act which is focused on the aspect of victim protection. This research uses a socio-legal approach. Considering that sexual violence can occur in any locations and even the perpetrators can be victims’ closest relatives. The substantive of the law is to provide protection to the victims, including victims of revenge porn which can be defined as the distribution of pornographic content as a form of revenge against victims. This is stated in Article 4 Paragraph 1 of the aforesaid act, that there are at least nine criminal acts of sexual violence. The Act on the Crime of Sexual Violence has been officially promulgated through the State Gazette after it was enacted in the Plenary Meeting on April 12, 2022. The passing of the law is a historic moment that has been long awaited by the public. The presence of regulation is considered to be an evidence of the struggle of victims. Therefore, it is very important to see the implications of the law from victim protection aspect, in addition to the law as a legal protection instrument for the victims of sexual violence. Keywords: Implications, Sexual Violence, Victim Protection.